Inhibition of DNA topoisomerases I and II and growth inhibition of HL-60 cells by novel acridine-based compounds - Janočková, Jana; Plšíková, Jana; Kašpárková, Jana; Brabec, Viktor; Jendželovský, Rastislav; Mikeš, Jaromír; Kovaľ, Ján; Hamuľaková, Slávka; Fedoročko, Peter; Kuča, Kamil; Kožurková, Mária (European journal of pharmaceutical sciences, 2015)
HL-60 cancer cells were treated with a series of novel acridine derivatives (derivatives 1-4) in order to test the compounds' ability to inhibit both cancer cell growth and topoisomerase I and II activity. Binding studies of derivatives 1-4 with calf thymus DNA were also performed using a number of techniques (UV-Vis and fluorescence spectroscopy, thermal denaturation, linear dichroism and viscometry) to determine the nature of the interaction between the compounds and ctDNA. The binding constants for the complexes of the studied acridine derivatives with DNA were calculated from UV-Vis spectroscopic titrations (K=3.1×10(4)-2.0×10(3)M(-1)). Some of the compounds showed a strong inhibitory effect against Topo II at the relatively low concentration of 5μM. Topo I/II inhibition mode assays were also performed and verified that the novel compounds are topoisomerase suppressors rather than poisons. The biological activities of derivatives were studied using MTT assay and flow cytometric methods (detection of mitochondrial membrane potential, measurement of cell viability) after 24 and 48h incubation. The ability of derivatives to impair cell proliferation was tested by an analysis of cell cycle distribution.
Keywords: farmaceutická chemie; proliferace buněk; vztah mezi dávkou a účinkem léčiva; HL-60 buňky; Acridines; Topoisomerase II Inhibitors; DNA-topoisomerasy typu II; vysoká teplota; Topoisomerase I Inhibitors; DNA Topoisomerases, Type I; Membrane Potential, Mitochondrial; akridiny; Hot Temperature; Time Factors; časové faktory; Leukemia, Promyelocytic, Acute; akutní promyelocytární leukemie; DNA; lidé; Cell Cycle Checkpoints; denaturace nukleových kyselin; Chemistry, Pharmaceutical; kontrolní body buněčného cyklu; inhibitory topoisomerasy II; spektrofotometrie ultrafialová; Nucleic Acid Conformation; DNA-binding; HL-60 Cells; HL-60 cells; Acridine derivatives; farmaceutická technologie; fluorescenční spektrometrie; konformace nukleové kyseliny; Topoisomerases I and II; Dose-Response Relationship, Drug; DNA-topoisomerasy I; membránový potenciál mitochondrií; Spectrophotometry, Ultraviolet; DNA Topoisomerases, Type II; Cell Proliferation; viskozita; Cell Survival; viabilita buněk; Nucleic Acid Denaturation; Spectrometry, Fluorescence; inhibitory topoisomerasy I; Viscosity; Technology, Pharmaceutical; Humans